Association of metastatic nodal size with survival in non-surgical non-small cell lung cancer patients: Recommendations for clinical N staging - Zhang, Yanan; Liu, Zhehui; Wang, Hongmin; Liang, Fengfan; Zhu, Liqiong; Liu, Haifeng (Frontiers in Oncology, 2022)
Background: This study aims to analyze the prognostic significance of the metastatic lymph node (mLN) size in non-small cell lung cancer (NSCLC) patients receiving chemoradiotherapy (CRT) to provide some information for the optimization of clinical nodal (cN) staging. Methods: A retrospective study with 325 NSCLC patients was conducted between January 2011 and December 2018 at two participating institutes. We evaluated the potential relationship between the mLN size and the survival to propose a potential revised nodal (rN) staging. Results: Kaplan–Meier analyses showed significant differences in the overall survival (OS) based on the cN staging and the size of mLNs (N0, ≤2 cm, and >2 cm). We found that the nodal size correlated statistically with the response to CRT. The HRs of OS for patients with bulky mLNs increase significantly compared with patients in the non-bulky mLNs group in the cN2-3 group. Interestingly, the HRs of patients with bulky cN2 disease and non-bulky cN3 disease were similar to each other. We classified the patients into five subsets: N0, rN1( cN1), rN2(non-bulky cN2), rN3a(bulky cN2, and non-bulky cN3), and rN3b(bulky cN3). In our study, the rN stage showed better prognostic discrimination than the 8th IASLC cN staging and was an independent prognostic factor for survival. Conclusions: In addition to the anatomic location, the size of mLNs correlated statistically with the response to CRT and should be incorporated into the cN staging system to predict survival more accurately.